Amateur radio communication technology evolution and issues in Malaysia - Johar, Azlee; Sheik Osman, Wan Rozaini; Ab. Aziz, Azizi (2016)
The adoption and use of wireless communication technology such as Amateur Radio Communication Technology (ARCT) have made the sharing and dissemination of information more easily achieved among community in particular situation.The evolution and issues in adoption of ARCT in Malaysia is discussed in this article.The study begins by making reference literature review which is related to ARCT.Qualitative research methodology is used to collect data, including participant involvement in Amateur Radio Community (ARC) program, casual interview among individual whose are related to ARCT and through review imperative article.The significance and passionately debated issues which are related to ARCT are also described in this article.